KAITAN SPIRITUAL INTELLIGENCE DENGAN PEMAKNAAN DAN PELAKSANAAN NILAI DI SEKOLAH - HANUM, FARIDA (Universitas Negeri Yogyakarta, 2003)
Every subject matters contains the elements of value and meaning, and is very good to give them to the students. Through this knowledge, they have been invited from the beginning to develop their spiritual intelligence. In order to develop the spiritual intelligence, the process of education should make the students to he common to ask